1505. Antiviral and Antibiotic Prescribing Among Patients at an Ambulatory Cancer Center with Laboratory-Confirmed Influenza. (31st December 2020) - Sorey, Woody; Krantz, Elizabeth M; Morris, Jessica; Klaassen, John; Sweet, Ania; Tverdek, Frank; Pergam, Steven A; Liu, Catherine
Abstract: Background: Cancer patients are at high risk for serious complications due to influenza. Early treatment with neuraminidase inhibitors (NAIs) is recommended for high-risk patients with suspected or documented influenza. Limited data exist on timing of presentation to care and ambulatory management of cancer patients with influenza. We sought to characterize antimicrobial prescribing and outcomes among patients with influenza at a large cancer center. Methods: We selected consecutive patients seen in the ambulatory cancer clinic with laboratory confirmed influenza between January 1, 2016 and December 31, 2018 for chart review. A lab-developed multiplex PCR assay was used with a turnaround time of about 24 hours. We obtained demographics, symptoms at first clinic encounter (day 0), viral testing, NAI and antibiotic prescribing, and clinical outcomes. Results: Of 138 charts reviewed, 133 (96%) were eligible for analysis. 109 (82%) had an underlying hematologic malignancy. 84 (63%) tested positive for influenza A and 49 for influenza B. 58 (44%) presented to care within 48 hours of symptom onset (F1). The most commonly reported symptoms were cough (83%), fever (41%), and rhinorrhea (40%) (F2). 110 (83%) were prescribed oseltamivir, with 24 (22%) receiving empiric therapy on day 0, and 63 (57%) prescribed on day 1 (F3). Among 109 patients with known symptom onset date, 34 (31%) were prescribed oseltamivir within 48 hours of symptom onset. 23 (17.3%) were prescribed antibiotics, 17 (74%) on day 0 (F3). Levofloxacin (26%), azithromycin (21%) and vancomycin (18%) were most commonly prescribed. Nine (6.8%) patients progressed to lower respiratory tract infection, 1 complicated by bacterial pneumonia. There were 11 (8.3%) influenza-related hospitalizations, 1 (0.7%) ICU admission, and no influenza-related deaths. Figure 1. Time From Symptom Onset to Date of First Clinical Encounter Figure 2. Symptoms Reported at First Clinical Encounter Figure 3. Time from First Clinical Encounter to Oseltamivir and Antibiotic Prescription Conclusion: NAIs were frequently prescribed among cancer patients, but less than a third received treatment within 48 hours of symptom onset. Most were prescribed NAIs only after test results were available, while antibiotics were prescribed empirically. Delayed presentation to care is an obstacle to early NAI use; patient and provider education along with rapid diagnostics are needed to improve early NAI use among cancer patients with influenza. Disclosures: Steven A. Pergam, MD, MPH, Chimerix, Inc (Scientific Research Study Investigator)Global Life Technologies, Inc. (Research Grant or Support)Merck & Co. (Scientific Research Study Investigator)Sanofi-Aventis (Other Financial or Material Support, Participate in clinical trial sponsored by NIAID (U01-AI132004); vaccines for this trial are provided by Sanofi-Aventis)